Investment Promotion and Regional Economic Intelligence: An Analysis of the Dakhla Oued Eddahab Regional Development Programme - Imane EL MAJJI; Mustapha OUKASSI (International Journal of Scientific Research and Innovative Studies, 2026)
In the context of the implementation of advanced regionalisation in Morocco, particularly in the southern provinces, and the adoption of new territorial development measures tailored to regional specificities, the analysis of Regional Development Programmes (RDPs) is essential. These programmes constitute strategic instruments aimed at enhancing the economic attractiveness of territories, whilst addressing the challenges of competitiveness, equity and sustainability. In this context, territorial economic intelligence (TEI) emerges as a key lever for supporting and optimising regional development policies. Applied to the Dakhla Oued Eddahab region, it helps to strengthen territorial competitiveness by promoting better use of local resources and facilitating the identification of investment opportunities. TEI is based on structured processes for the collection, analysis and dissemination of strategic information, enabling informed decision-making and the coordination of actions by various public and private stakeholders. By integrating this approach into the RDP, the Dakhla Oued Eddahab region benefits from a more coherent regional governance framework, based on synergy between institutions, businesses and local stakeholders. This approach promotes investment, stimulates innovation and supports the development of productive activities, thereby contributing to sustainable and inclusive economic growth, as well as to the reduction of territorial disparities. The aim of this research is to highlight the role of territorial economic intelligence (TEI) in the strategic positioning and promotion of the attractiveness of the Dakhla Oued Eddahab region. To this end, a forward-looking approach is employed to analyse the region’s socio-economic characteristics and evaluate the RDP as a tool for strategic territorial planning. By 2030, territorial economic intelligence will be at the heart of economic diplomacy and territorial development policies, with an enhanced role for investment support institutions, notably the Regional Investment Centres. Keywords: Territorial economic intelligence (TEI); regional development; territorial attractiveness; investment promotion; territorial governance. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/633